Aplication of Value Engineering in Bamboo Chair Product Design Development for Foreign Market - Wahyu Purwanto (agriTECH, 2003)
In this research. bamboo chair design development was based on Value Engineering approach, which consisted of three stage, information stage as consumer needs identification stage. creativity stage as concept building stage and analyzed stage as concept judgment stage. The development aspects in this research were related to aesthetic aspects _function especially shape and color of chair. The alternatives were developed based on variety of shape and bamboo. The strengths and the weaknesses of each alternative were analyzed in relation with other aspects before they were used in concept building. There were 14 product concepts as concept building stage output. The best concept is the concept with highest value. Value was defined as function per cost. In this research, function was product performance that was appreciated by consumer while cost was variable production cost, fared cost was not included because it was assumed equal for each concept. Based on that equation, the best product concept was the bamboo chair in peg appendix, square seat square back of chair in incline position, straight-arm of chair and not connected with front leg of chair, and the material is opus bamboo. The value of this alternative was 3.89.10, while market product was 2,90.10- 3, it means there was an improvement.